WORK LIFE BALANCE IBU BEKERJA YANG MEMPUNYAI ANAK USIA DINI SELAMA PANDEMI - Brigita Ivana; Wieka Dyah Partasari (MANASA, 2023)
The aim of this research is to see working mother’s work life balance with early childhood childrenduring work from home era due to the COVID-19 pandemic. This research uses a qualitativephenomenological method with semi-structured interviews and thematic analysis. Participantsconsisted of 3 working mothers that have a child or children around 3-5 years old, work in acompany owned by another party at least 40 hours a week, and currently doing work from home.Participants were chosen using purposeful sampling homogeneous method. Analysis showsdifferent levels of work life balance between all three participants, and only one of them experiencework life balance. These differences influenced by factors such as participant’s career aspiration,types of job, support from partner and family, as well as the partner’s type of work. Therecommendation for future research is to look for the impact of partner’s type of work to theintensity of parenting task distribution. Future research can also look for the impact of careeraspiration to working mother’s satisfaction and work life balance. In an era where remote workis increasingly common, this research is expected to provide an overview of how working mothersdivide their roles, so that companies can make policies based on this situation. The research isalso expected to be useful for career women who are not married or do not have children yet to beable to plan a more mature future with their partner, both in the context of role division and mentalreadiness.